Impact on safety stock due to the use of the standard deviation of forecast errors - Arias-Vargas, Marco (2017)
It is common to use the standard deviation of the historical data in safety stock calculations, but this is the same as assuming that the forecasting model will be a simple average, thus this can lead to an unnecessary increase in the safety stock investment.  In order to avoid that situation, the standard deviation  of the forecasts errors must be used, and this, along with the right selection of the forecasting model, will lead to a reduction in the safety stock, maintaining the same service level.  The impact of the mentioned reduction in this investment could be high as in the examples of two companies shown in this article, where they have opportunities of reductions of more than 40% in the safety stock.